Activity profiles by position in youth elite soccer players in official matches - Pettersen, S. A.; Brenn, T. (Sports Medicine International Open, 2019)
In order to investigate activity profiles and external load patterns in elite youth soccer players, we studied high-intensity activity patterns, maximum running speed, and temporary and end-of-match decline in external load in 54 U17 players (96 match observations) over a full season of official match play.